Study on Relationship of Psychopathology on Childhood Obesity Among School Children in South India - Kumar, Dodderi Sunil; Shenoy, Bhaskar; Raju, Mahabala; Pallakki, Savitha (International Journal of Child Health and Nutrition, 2013)
Study on relationship of psychopathology on childhood obesity among school children in South India. Aim: To study the relationship of psychopathology on obesity among school children of Davangere district, South India. Settings and Design: School children studying in V-VII standard of Davangere dist in Karnataka, south India. Stage-I cross sectional study for identification of obese children. Stage-II Case control study to find out the relationship of psychopathology and obesity among school children. Material and Methods: Body mass index (BMI) was calculated using BMI charts based on NCHS standards. 421 obese children and 842 controls (1:2 ratios) were studied by using Childhood Psychopathology Measurement Schedule (CPMS) tool developed and standardized by Malhotra et al. Statistical Analysis: Data analysis was conducted at SPSS/ PC programme (Version 13). Results and Conclusions: The psychopathology was present in 44.2% of obese children by using CPMS tool as against only 13.8% of non obese children. The presence of psychopathology among obese boys was more (59.5%) than obese girls (49.4%). The obese children had the relationship of psychopathology 4.9 times more than nonobese children. The positive association of psychopathology with obesity was present in both sexes. The association was found to be stronger for boys in comparison to girls. Our study findings show that psychopathology has strong relationship on obesity among school children and psychopathology has a definite impact on childhood obesity.